Dielectric materials development using bio-waste: A review - Norazwina, Zainol; Nurfarhana, Mustafa; Nor Hazwani, Aziz; Azahani Natasha, Azman; Mohamad Shaiful, Abdul Karim (BioMed Central Ltd., 2021)
The increasing global demand for food due to population expansion has led to the intensifcation of the agricultural sector. However, this escalation in agricultural production has brought together undesirable consequences as more waste is produced, leading to growing environmental concerns as proper disposal of these wastes is necessary. Valorization of these bio-wastes into dielectric materials ofers a promising solution to conventional, non-renewable, yet costly materials. Comprehensive documentation on the development of these wastes into dielectric materials is then necessary to understand their dielectric properties and how these materials behave with the treatments during the fabrication process. This review focuses on the stateof-the-art development of dielectric materials derived from bio-wastes and agricultural waste, which are benefcial for waste management and materials engineering applications. The elemental composition of the waste materials is also discussed in this review to understand its relationship with the dielectric constant. Moreover, the fabrication process for several waste materials into dielectric materials has been provided and compared. This review provides comprehensive information on green materials in the materials engineering industries and can assist in novel studies. It is foreseen that bio-wastes and agricultural wastes can be renewable, sustainable, and low-cost resources for deriving dielectric materials in light of their ease of accessibility.